MENDORONG KEBERLANJUTAN BISNIS MELALUI PAJAK KARBON, KINERJA LINGKUNGAN, DAN CORPORATE SOCIAL RESPONSIBILITY - Romlah, Siti; Nopianti, Rina; Pertiwi, Sari Putri (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
This study aims to analyze the role of carbon tax, environmental performance, and corporate social responsibility (CSR) in driving business sustainability among mining companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The sample consists of 12 mining companies selected using purposive sampling over five years. The independent variables include carbon tax, environmental performance (measured by the PROPER index), and CSR (measured using a disclosure dummy). Business sustainability is proxied by Return on Assets (ROA) as an indicator of profitability. The multiple linear regression analysis shows that carbon tax, environmental performance, and CSR do not have a significant effect on business sustainability (ROA). These findings indicate that during the observed period, environmental policies and CSR initiatives have not been sufficiently effective in enhancing sustainable profitability in the mining sector.